Early Postoperative Complications in Colorectal Cancer Patients Following Colorectal Surgery Among Yemeni Patients: A Prospective Study - Al-Amry AL; Obadiel YA; Al-Shehari MM; Gailan WM; Bajubair MH; Jowah HM (Open Access Surgery, 2024)
Ali Lotf Al-Amry,1,2 Yasser Abdurabo Obadiel,1,2 Mohammed Mohammed Al-Shehari,1,2 Waleed Mohammed Gailan,1,3 Mohammed Hadi Bajubair,3 Haitham Mohammed Jowah1,2 1Department of Surgery, Faculty of Medicine and Health Sciences, Sana’a University, Sana’a, Yemen; 2Department of Surgery, Al-Thawra Modern General Hospital, Sana’a City, Yemen; 3Department of Surgery, Kuwait University Hospital, Sana’a City, YemenCorrespondence: Haitham Mohammed Jowah, Department of Surgery, Faculty of Medicine and Health Sciences, Sana’a University, Sana’a City, Yemen, Tel +967774831058, Email h.jowah@su.edu.yePurpose: This prospective study aimed to investigate the early outcomes of colorectal surgery in patients with colorectal cancer and determine their relationships with specific risk factors and comorbidities.Patients and Methods: This study was conducted at AL-Thawra Modern General Hospital and Kuwait University Hospital in Sana’a, Yemen, from January 2021 to December 2022. All consecutive patients who underwent surgical intervention for colorectal cancer were included. Data on patient demographics, comorbidities, tumor characteristics, surgical procedures, and postoperative outcomes were collected.Results: A total of 73 patients, with a mean age of 52.5 years (SD = 14.3), were included in the study. Among the patients, 44 (60.3%) were male, and 29 (39.7%) were female. The most frequent complication observed was surgical site infection, which occurred in 13 (17.8%) patients, primarily as superficial infections in 11 (15.1%) patients. Other local complications included wound dehiscence, anastomotic leakage, paralytic ileus, and abdominal sepsis. Systemic complications, such as pneumonia, deep vein thrombosis, acute myocardial infarction, and urinary tract infection, were observed in 9 patients. Significant associations were found between the development of early postoperative complications and various factors. Patients aged 65 years and above had a greater rate of complications than did those aged younger than 65 years (55% vs 22.6%, p value = 0.008). Furthermore, the presence of diabetes mellitus and low serum ALB levels (< 35 g/L) were associated with increased complication rates (60% vs 24.1%, p value = 0.01 and 42.9% vs 8.3%, p value = 0.02, respectively).Conclusion: Our study demonstrated favorable outcomes with no mortality and a comparable complication rate to other studies, despite the smaller sample size. The significant associations between postoperative complications, advanced age, diabetes mellitus, and low serum ALB levels highlight the importance of a multidisciplinary approach to enhancing overall patient outcomes.Plain Language Summary: This study examined the outcomes of surgery for colorectal cancer in Yemeni patients and examined factors that could affect these outcomes. The researchers studied 73 patients who underwent surgery for colorectal cancer. The average age of the patients was 52.5 years, and there were slightly more male patients than female patients. The most common complication after surgery was infection at the surgical site, which affected 17.8% of patients. Other complications included problems with wound healing, leakage at the surgical connection, difficulty with bowel movement, and infection in the abdomen. A small number of patients also experienced complications in other parts of their body, such as pneumonia, blood clots, heart attack, and urinary tract infection.The study revealed that older patients aged 65 years and older had a greater risk of complications than younger patients. Patients with diabetes and low levels of a protein called albumin in their blood were also more likely to have complications after surgery.In conclusion, this study showed that surgery for colorectal cancer in Yemeni patients had overall good outcomes, with no deaths reported. However, older age, diabetes, and low ALB levels were identified as risk factors for complications. The findings highlight the importance of a team approach to healthcare to improve outcomes, especially for older patients and those with diabetes or low albumin levels. This information can help healthcare providers in Yemen better care for patients undergoing colorectal cancer surgery and reduce the risk of complications.Keywords: colorectal cancer, surgical resection, operative complications, morbidity, mortality, Yemen